EFFECTIVENESS OF ROLE PLAYING LEARNING STRATEGY ON MATHEMATICS LEARNING OUTCOMES OF CLASS VII STUDENTS OF SMPN 1 SEMPOR, KEBUMEN DISTRICT - Linda Puspita; Nur Arina Hidayati (Universitas Ahmad Dahlan, 2017)
The lack of attention given to the materials the students by the teacher in the learning outcome processed studied mathematics students. One of the learning strategies that focus student against teacher is Role Playing learning strategies. The purpose of this research is to know the effectiveness of learning strategies among students who are using Role Playing learning strategies with students who use direct learning outcomes learning mathematics in grade VII semester odd SMP Negeri 1 Kebumen Regency Sempor school year 2016/2017. This research population is grade VII SMP Negeri 1 Kebumen Regency Sempor school year 2016/2017, with a total of 256 students. Penelitaian is a sample class VII A and VII B as a class experiment and control that is selected by random sampling against class. Method of collecting data using the method of documentation and tests. Research instrument in the form of a test of the ability of the beginning and test results of learning math. Data analysis is a test of the hypothesis. Hypothesis test results of two parties with the significance level 5% and 62 degrees of freedom shows that: (1) there is a difference in the results of learning math learning strategies that use Role-Playing with Direct learning. This is shown on = and 1.86763 = 3.0869 so > and (2) Learning Mathematics using Role Playing strategy is more effective than Direct learning. This is shown by the value = 3.0869 and = 1.6702, > value.